A Case of Perforation of Diverticulum of the Third Duodenal Part due to Ileus Tube - Matsumoto, Joe; Hirano, Satoshi; Kojima, Tetsufumi; Hiraguchi, Etsuro; Murakami, Takahisa; Domen, Hiromitsu; Konishi, Kazuya; Kondo, Satoshi (Nippon Shokaki Geka Gakkai zasshi, 2006)
We report a case of perforation of the diverticulum of the third duodenal part due to insertion of an ileus tube. A 79-year-old woman who had undergone laparotomy 3 times was admitted with a diagnosis of ileus. Abdominal CT showed enlargement of the small bowel and a tumor in the ascending colon. On hospital day 1, a long tube was inserted to release ileus, but could not be inserted to the jejunum. On hospital day 2, fluoroscopy via the tube showed leaks of contrast medium from the 2nd portion of the duodenum, necessitating emergency surgery under a diagnosis of duodenal perforation due to ileus tube. In operative findings, the long tube was pushed out extraluminally into the retroperitoneal space from the diverticulum in the proximal of 3rd portion. The diverticulm was resected and a drainage tube inserted together with right hemicolectomy for the colictumor. This is, to our knowledge, the first report of perforation of the duodenal diverticulum due to insertion of an ileus tube.